Histamine and histamine receptors: Roles in major depressive disorder - Qian, Hong; Shu, Chang; Xiao, Ling; Wang, Gaohua (Frontiers in Psychiatry, 2022)
Although the incidence of major depressive disorder is high and its social impact is great, we still know very little about the pathophysiology of depression. The monoamine hypothesis of depression suggests that 5-HT, NE and DA synergistically affect mood, which is the basis of current drug therapy for depression. However, histamine as a monoamine transmitter is rarely studied. Our review is the first time to illustrate the effect of histaminergic system on depression in order to find the way for the development of new antidepressant drugs. The brain neurotransmitter histamine is involved in MDD, and the brain histaminergic system operates through four receptors. Histamine and its receptors can also regulate the immune response to improve symptoms of depression. In addition, H3R can interact with other depression-related transmitters (including 5-HT, DA, GLU, and MCH); thus, histamine may participate in the occurrence of depression through other neural circuits. Notably, in rodent studies, several H3R and H1R antagonists were found to be safe and effective in alleviating depression-like behavior. To highlight the complex functions of histamine in depression, and reveals that histamine receptors can be used as new targets for antidepressant therapy.